Methodology of problematization with the maguerez’s arch: an alternative method for teaching, research and study in dentistry - Heleine Maria Chagas Rêgo; José roberto Rodrigues (Brazilian Dental Science)
Objective: evaluate the application of the problematization methodology(PM) (Arch Maguerez), as an alternative teaching-learning method in formation post-graduation students. Material and Methods: 25 post-graduate students of  the program in Restorative Dentistry at the  School of Dentistry of ICT-Office of Science and Technology of São José dos Campos, São Paulo State University – UNESP, who were part of the discipline of Applied Teaching Higher Education , developed activities that characterized the problematization methodology (PM) and the traditional teaching methodology in force. By means of a questionnaire it was possible to assess the perception the students had of the activities made. Results: It was observed that problematization methodology (PM) was a valid alternative teaching-learning method for formation of new professors, in the opinion of students. Conclusion: problematization methodology (PM) can be applied as a complementary tool in the construction of the future professors’ knowledge, in addition to being a strategy for research and study.